Short-term hand-held vibration training benefits handgrip strength in competitive judokas - Hawkey, A. (Journal of Sport and Human Performance, 2019)
Handgrip strength (HGS) is fundamental in judo as judokas hold their opponent`s judogi (uniform) throughout a contest. Therefore, maximising HGS in this specialist population is crucial to successful performance. Judokas have traditionally performed grip curl exercises to improve HGS. While recent research has investigated hand-held vibration training (HHVT) as an ergogenic aid this research is limited and to date there have been no studies assessing the efficacy of HHVT in judo. Following institutional ethics approval, 12 male competitive judokas (age mean 22 ±8years, mass mean 81 ± 18kg, height mean 1.73 ±0.43m) were randomly assigned to either a HHVT (n=6) or control (n=6) group. Judokas in the HHVT group were exposed to three bouts of vibration, on each hand, twice a week for a four-week period. Frequency and training time were consistent with the overload training principle. Control group performed the same isometric contractions with no vibratory stimulus. Throughout the study, both groups continued with their usual training. Prior to commencement, and following completion, of the study all judokas had their HGS measured using a handgrip dynamometer. Repeated measures ANOVA revealed a significant improvement (P<0.001) over time in the pre and post HGS of both conditions combined and a significant improvement (P=0.023) in the HGS of the HHVT condition. No significant effects (P>0.05) were found in regard to handedness. Judokas should therefore consider incorporating HHVT into their training regimes. However, future research should further investigate optimal exposure frequencies and training durations for HHVT in a judo population.